THE ROLE OF SIM IN THE FINANCIAL INDUSTRY (BRIMO APP) - Dewi Puspaningtyas Faeni; Lufiana Anggrainie (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
Management Information System (MIS) is one of the key technologies in improving operational efficiency and effectiveness in various industry sectors, including the financial industry. The BRImo application developed by Bank Rakyat Indonesia (BRI) is an example of innovative SIM implementation in the banking sector. BRImoprovides various financial services that are easily accessible to customers through mobile devices. This study analyzes the use of BRImo as a SIM in the financial industry, identifying the main benefits perceived by customers and institutions, as well as the challenges faced in its implementation. The results show that BRImo has successfully improved customer convenience and satisfaction, bank operational efficiency, and expanded the range of banking services. However, there are challenges related to data security and technology adaptation by users. Therefore, careful plans and procedures a r e required to optimize the use of SIM in the financial industry, especially through the BRImo application.